Developing effective local content regulations in sub-Sahara Africa: The need for more effective policy alignment. Issue 4 (12th December 2016) - Ayentimi, Desmond Tutu; Burgess, John; Brown, Kerry
Abstract : Purpose: The authors propose a strategic-balance approach to local content laws in which less developed economies in sub-Sahara Africa can develop investment incentive policies for attracting multinationals and direct foreign investment but, at the same time, have a structured and operational framework for the enforcement of local content laws. The purpose of the paper is to identify the elements involved in the equation: the incentives, the potential spillovers and the criteria for evaluation. Design/methodology/approach: The approach involves a review of the literature and the operational details and limitations of local content laws in sub-Sahara Africa. Findings: The paper develops a conceptual model for a holistic understanding and management of this dilemma by policymakers and development practitioners to maximize the benefits of natural resources to less developed countries in sub-Sahara Africa towards the fight against poverty and underdevelopment. Research limitations/implications: This paper provides the opportunity to influence policy direction in relation to the adoption of investment incentive policies and programs and the enforcement of local content policy guidelines and regulations in sub-Sahara Africa. Practical implications: Multinational companies (MNCs) operating in less developed and emerging economies in sub-Sahara Africa should consider how their economic and corporate social responsibility activities can help develop the capabilities of the local workforce through training and development activities; develop domestic firms' capabilities via enterprise development programs; and develop local firm's absorptive capacities through knowledge transfers and innovation systems to support development activities. Social implications: Policymakers in less developed and emerging economies in sub-Sahara Africa need to strike a balance in adopting investment incentives policies towards attracting foreign investments and the enforcement of local content regulations to make sure they derive the maximum benefits from their strategic resources. It is important for policymakers to understand that the mere attraction of MNCs into an economy does not explicitly guarantee domestic job creation; rather, it depends on how MNCs respond to local content policy regulations through their business strategies. Linking investment incentives with local content policy regulations at a critical point could potentially support and strengthen industrial development in sub-Sahara Africa. Originality/value: This paper is among the first to examine the challenges of both attracting foreign direct investment and enforcing local content laws and regulations in sub-Sahara Africa. This paper contributes to the understanding of this dilemma and how less developed economies can manage such a crucial and important issue using our proposed strategic-balance approach. The contribution of local content laws and the design and adoption of investment incentives policies and programs to attract foreign investment to promoting sustainable domestic growth and development must depend on the balance between the enforcement of local content policy guidelines and the provision of such investment incentive packages to attracting foreign investment.